El decadentismo en la derecha radical contemporánea - Simón Gómez, Miguel Ángel (Política y Sociedad, 2007)
The main concern this articles deals with is, first, the elusive conceptual definition of the «radical right». In the last years a, so called, new consensus, has been developed in the literature of this field. The core of this new consensus about the radical right is the palingentic form of nationalism, form this pant of view the decadentism and the claim for a social renewal is a central point in the political thought of the radical right. In this article we deal with the decadent subjects of the radical right, pointing mainly to the apocalyptic tone of some major contributors of the radical right in the interwar France and Germany. In the second part we analyze the role of decadentism in the cotemporary work of some relevant authors of the European radical right, Alain de Benoist and Julius Evola. Finally we translate their idea of decadence of Europe to the political arena as shown the discourses of some right extremist European parties.